Developing and Assessing a Holistic eLearning 4.0 Model for Higher Education in Saudi Arabia - Alnassar, Mohammad Ahmad N. (Curtin University, 2023)
There is a lack of models that may facilitate the successful and effective application of eLearning 4.0 in Saudi Arabia. The purpose of this study is to bridge these research gaps by offering an eLearning 4.0 model and recommendations as a road map for stakeholders in light of eLearning 4.0's relatively recent appearance. A holistic eLearning 4.0 model was proposed to facilitate the integration of eLearning 4.0 and its technologies in the higher education sector.